(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to shed light on the problems that the student-teacher may face and that affect his preparation and thus the educational process. In the Department of Mathematics, a number of previous studies have been approved, the most important of which were the researcher’s access to the sources and literature of previous studies related to the subject of the research.